A review of nonlinear fluid models for ion-and electron-acoustic solitons and double layers: Application to weak double layers and electrostatic solitary waves in the solar wind and the lunar wake - Lakhina, G. S.; Singh, S. V.; Rubia, R.; Sreeraj, T. (My University, 2018)
Electrostatic solitary waves (ESWs) have been observed in the Earth's magnetosphere, solar wind, lunar wake, and also in other planetary magnetospheres. The observed characteristics of the ESWs have been interpreted in terms of models based either on Bernstein-Green-Kruskal (BGK) modes/phase space holes or ion- and electron-acoustic solitons. However, the space community has favored the models based on BGK modes/phase space holes. In this review, current understanding of the fluid models for ion-and electron-acoustic solitons and double layers in multi-component plasmas is presented. The relationship between the theoretical models and space observations of ESWs is emphasized. Two specific applications of ion- and electron-acoustic solitons to the occurrence of weak double layers and coherent electrostatic waves in the solar wind and the lunar wake are discussed by comparing the observations and theoretical predictions. It is concluded that models based on ion- and electron-acoustic solitons/double layers provide a plausible interpretation for the ESWs observed in space plasmas.
Keywords: Solar wind; Electron acoustic solitons; Electrostatic solitary waves; Ion-acoustic solitons; Lunar wake